Infantile spasm clinical profile - kareem, adil (Karbala Journal of Medicine, 2019)
Background: Infantile spasms usually associated with psychomotor regression and unique interictal electroencephalogram (EEG) pattern known as hypsarrhythmia. West syndrome is often used in the presence of this triad however is considered disasters to the patients due to the wide range of sequelae that including intractable epilepsy, psychomotor delay, pervasive developmental disorder. Objective: to study clinical profile, EEG and treatment response for infantile spasm. Patient and method: Fifty six patients with infantile spasm have been enrolled in the study who seeks medical advice in our hospital with onset of spasm between 1-12 month age and shows significant finding when EEG done for they and consequently at least 2 years period follow up. Result; A total of 55 consecutive cases of infantile spasms with significant finding in their EEG were recorded; male to female ratio is 57%:43%. Structural defect in the brain was the predominant cause. 16% of children, the reason had not been proven. The Outcome was only favorable in 5 (11%) of children. many variable like age of onset, sex, lag time and co-morbidity were not significant and did not affect final outcome. Conclusion; The current study highlights the clinical profile of children with infantile spasm, in term of delayed diagnosis, etiology of structural brain defect, and favorable response to steroids.